CP-140 Spontaneous resistance to temocillin, an old and rarely-used antibiotic indicated for the treatment of multiresistant Enterobacteriaceae infections: a case report. (24th February 2014) - Tron, C; Surugue, J
Abstract : Background: Temocillin is an antibiotic with high beta-lactamase stability. Its activity is limited to Enterobacteriaceae. Studies showed that temocillin rarely selects resistant mutants while carbapenem efficacy against extended-spectrum beta lactamase (ESBL)-producing Enterobacteriaceae may be challenged by emerging resistant carbapenemase-producing strains. The antibiotic appears to be an effective alternative to carbapenem. Currently, temocillin is marketed in the United Kingdom and Belgium. In France, the antibiotic can only be supplied on approval of the National Medicines Agency (ANSM) for named patients. This process explains the limited use of temocillin in France and the low levels of minimum inhibitory concentration (MIC) expected for this antimicrobial agent. Purpose: To describe a case of spontaneous resistance to temocillin. Materials and methods: A 78-year-old man was hospitalised for 79 days in the intensive care unit because of several infectious episodes. His medical record was reviewed with a focus on drug treatments and microbiological laboratory results in the light of published temocillin studies and literature data on multidrug-resistant bacteria. Results: The patient was found colonised by a nosocomial multiresistant ESLB and cephalosporinase-producing Klebsiella pneumoniae which caused septicaemia. He was first treated with carbapenem. In accordance with antibiotic stewardship to spare carbapenem in case of further infections, the susceptibility of the strain to temocillin was tested. An unexpectedly high MIC value of 96 µg/mL (usual range between 8–32 µg/mL) revealed the resistance of the strain to the alternative antibiotic. Conclusions: Temocillin was found resistant to ESBL-producing Klebsiella pneumoniae while sensitivity was expected. This underlines the necessity of careful antibiotic stewardship in complicated cases and multi-drug resistance, keeping in mind that drugs saved as spare alternatives may not demonstrate the expected efficacy in contaminated environments. This potential limitation of therapeutic options should always be anticipated to avoid an absence of antibiotic treatment options for our infectious patients. No conflict of interest.